Hydranencephaly - Pant, S; Kaur, G; De, JK (Kathmandu University Medical Journal, 2010)
Hydranencephaly is a rare congenital condition where the greater portions of the cerebral hemispheres and the corpus striatum are replaced by cerebrospinal fluid and glial tissue. The meninges and the skull are well formed, which is consistent with earlier normal embryogenesis of the telencephalon. Bilateral occlusion of the internal carotid arteries in utero is a potential mechanism. Clinical features include intact brainstem reflexes without evidence of higher cortical activity. The infant's head size and the spontaneous reflexes such as sucking, swallowing, crying, and moving the arms and legs may all seem normal at birth. However, after a few weeks the infant usually becomes irritable and has increased muscle tone and after a few months of life, seizures and hydrocephalus (excessive accumulation of cerebrospinal fluid in the brain) may develop. Other symptoms may include visual impairment, lack of growth, deafness, blindness, spastic quadriparesis (paralysis), and intellectual deficits. Since the early behaviour appears to be relatively normal, the diagnosis may be delayed for months sometimes. There is no definitive treatment for hydranencephaly. The outlook for children with hydranencephaly is generally poor, and many children with this disorder die before their first birthday. Key words: hydranencephaly; congenital anomaly; vascular disruption; thromboplastin DOI: 10.3126/kumj.v8i1.3227 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 83-86